2017
DOI: 10.1186/s12993-017-0124-5
|View full text |Cite
|
Sign up to set email alerts
|

Brain structural investigation and hippocampal tractography in medication overuse headache: a native space analysis

Abstract: BackgroundSpatial normalization of brain images, a prerequisite for voxel based morphometry analysis, may account for the large variability of the volumetric data in medication overuse headache (MOH); possibly because this disease concerns patients differing on both sex and age, and hence with different brain size and shape.MethodsThe present study aimed at providing a subject-based analysis of macrostructure using a native space volumes segmentation (Freesurfer), and microstructure using a region of interest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Furthermore, the volume of the periaqueductal grey matter of the midbrain was also significantly increased in these patients, which was positively correlated with more migrainerelated disability and higher levels of anxiety. An increase in GMV was also found bilaterally in the thalamus and ventral striatum, while a significant decrease was detected in the frontal regions including the orbitofrontal cortex, anterior cingulate cortex, left and right insula, and precuneus [57][58][59].…”
Section: Functional and Structural Changes In The Limbic System In Ch...mentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, the volume of the periaqueductal grey matter of the midbrain was also significantly increased in these patients, which was positively correlated with more migrainerelated disability and higher levels of anxiety. An increase in GMV was also found bilaterally in the thalamus and ventral striatum, while a significant decrease was detected in the frontal regions including the orbitofrontal cortex, anterior cingulate cortex, left and right insula, and precuneus [57][58][59].…”
Section: Functional and Structural Changes In The Limbic System In Ch...mentioning
confidence: 87%
“…In another study on MOH patients, it was found that the volumes of the superior temporal, fusiform, and occipital middle gyrus of the left hemisphere were decreased while the volume of the left inferior temporal/lateral ventricle and middle frontal sulcus were increased. The left temporal superior gyrus volume was negatively correlated with depression scores, number of medications taken per month, and medication dependence scores [57].…”
Section: Functional and Structural Changes In The Limbic System In Ch...mentioning
confidence: 93%